PENGARUH INDEKS SAHAM SYARIAH INTERNASIONAL DAN MAKROEKONOMI TERHADAP HARGA JAKARTA ISLAMIC INDEX - Rizki Afrinal, (2023)
The number of investors in the Indonesian Islamic capital market has increased during 2020. Nonetheless, the Islamic stock price index in Indonesia has decreased. The decline in share prices is similar to what happened in world capital markets. The decline in share prices was caused by macroeconomic shocks both in Indonesia and the world due to the Covid-19 pandemic. This study aims to determine the effect of international sharia stock indexes and macroeconomics on the price of the Jakarta Islamic Index. This study uses the Dow Jones Islamic Market World Index (DJIM), S&P 500 Shariah (SPSHX), and FTSE All-World Sharia Index (FTSES) as variables that represent international Islamic stock indices as well as interest rates (IR), inflation, and exchange rates. (ER) as a variable that represents Indonesia's macroeconomic conditions. Using the Vector Error Correction Model (VECM) method, this study shows that inflation, exchange rates, DJIM, SPSHX and FTSES have a significant effect on JII in the long term, whereas in the short term only inflation and interest rates have a significant effect on JII. This study has limitations in terms of the variables used and is only able to describe 66% of the price of the Jakarta Islamic Index (based on the R-Squared value). For this reason, this research can be used as a literature review for further research by perfecting this research in terms of adding the variables studied.